Do flexicurity policies protect workers from the adverse health consequences of temporary employment? A cross-national comparative analysis. (December 2016) - Shahidi, Faraz Vahid; De Moortel, Deborah; Muntaner, Carles; Davis, Owen; Siddiqi, Arjumand
Abstract: Flexicurity policies comprise a relatively novel approach to the regulation of work and welfare that aims to combine labour market flexibility with social security. Advocates of this approach argue that, by striking the right balance between flexibility and security, flexicurity policies allow firms to take advantage of loose contractual arrangements in an increasingly competitive economic environment while simultaneously protecting workers from the adverse health and social consequences of flexible forms of employment. In this study, we use multilevel Poisson regression models to test the theoretical claim of the flexicurity approach using data for 23 countries across three waves of the European Social Survey. We construct an institutional typology of labour market regulation and social security to evaluate whether inequalities in self-reported health and limiting longstanding illness between temporary workers and their permanent counterparts are smaller in countries that most closely approximate the ideal type described by advocates of the flexicurity approach. Our results indicate that, while the association between temporary employment and health varies across countries, institutional configurations of labour market regulation and social security do not provide a meaningful explanation for this cross-national variation. Contrary to the expectations of the flexicurity hypothesis, our data do not indicate that employment-related inequalities are smaller in countries that approximate the flexicurity approach. We discuss potential explanations for these findings and conclude that there remains a relative lack of evidence in support of the theoretical claims of the flexicurity approach. Highlights: Temporary employment is associated with adverse health outcomes. Flexicurity policies are assumed to protect temporary workers. Flexicurity policies did not moderate the health impact of temporary employment. Evidence in support of the flexicurity approach remains lacking.